Implementing DSWD’s Supplemental Feeding Program in Urban Daycare Centers: A Qualitative Case Study of Barangay Zone 42, City of Manila - Edmund De Guzman; Danielle M De Guzman; Rishirl Alberto Cuario; Odranreb E Guillermo; Karlos Guererro D Zaragoza; Jhoanna Andrea E De Leon (Research Synergy Foundation, 2026)
Child malnutrition in the Philippines is not simply a nutrition problem—it is, at its core, a governance problem. The country has invested heavily in feeding programs for decades, yet children in many low-income urban communities still go without adequate nutrition. This paper examines the Department of Social Welfare and Development’s Supplemental Feeding Program (SFP) as it operates on the ground in daycare centers of Barangay Zone 42, Manila. The central research question is: how does inter-agency governance shape SFP implementation quality at the daycare center level in an urban poor community? Through a qualitative case study—fifteen stakeholder interviews and systematic documentary review—the research uncovered a program that delivers perceived nutritional and social benefits to enrolled children, while being hampered at nearly every turn by coordination failures between agencies, a food budget frozen in time while prices rose, and a parent education component that exists almost entirely on paper. The researchers argue that incremental fixes will not be enough; what the program requires is a fundamental rethinking of how DSWD and Manila City work together as genuine partners rather than as a compliance hierarchy.